2016
DOI: 10.7717/peerj.2807
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal monitoring of deep-sea communities using metabarcoding of sediment DNA and RNA

Abstract: We assessed spatio-temporal patterns of diversity in deep-sea sediment communities using metabarcoding. We chose a recently developed eukaryotic marker based on the v7 region of the 18S rRNA gene. Our study was performed in a submarine canyon and its adjacent slope in the Northwestern Mediterranean Sea, sampled along a depth gradient at two different seasons. We found a total of 5,569 molecular operational taxonomic units (MOTUs), dominated by Metazoa, Alveolata and Rhizaria. Among metazoans, Nematoda, Arthrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
103
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(114 citation statements)
references
References 93 publications
(151 reference statements)
11
103
0
Order By: Relevance
“…For instance, the clustering of mOTUs at 97% similarity resulted in a much higher number of taxonomic units than the morphological approach. The higher diversity observed with molecular data has previously been observed (e.g., Dell'Anno, Carugati, Corinaldesi, Riccioni, & Danovaro, ; Guardiola et al., ). While a higher diversity is observed in the molecular data, species assignments at the mOTU level are often currently unachievable.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…For instance, the clustering of mOTUs at 97% similarity resulted in a much higher number of taxonomic units than the morphological approach. The higher diversity observed with molecular data has previously been observed (e.g., Dell'Anno, Carugati, Corinaldesi, Riccioni, & Danovaro, ; Guardiola et al., ). While a higher diversity is observed in the molecular data, species assignments at the mOTU level are often currently unachievable.…”
Section: Discussionsupporting
confidence: 62%
“…The higher diversity observed with molecular data has previously been observed (e.g., Dell'Anno, Carugati, Corinaldesi, Riccioni, & Danovaro, 2015;Guardiola et al, 2016). While a higher diversity is observed in the molecular data, species assignments at the mOTU level are often currently unachievable.…”
Section: Comparison Of Traditional and Molecular Approachesmentioning
confidence: 65%
“…In applied settings, eDNA metabarcoding of surface sediments has revealed benthic impacts of aquaculture for Atlantic salmon farming on short spatial scales using both eDNA and eRNA (Pawlowski, Esling, Lejzerowicz, Cedhagen, & Wilding, 2014). Guardiola et al (2016) showed through a comparison of eDNA and eRNA that spatial trends in species richness from these two sources were similar, but that eDNA detected higher diversity. Overall, the fate, transport and decomposition of animal and plant eDNA in marine environments are poorly known compared to other environments, and there is pressing need for further studies.…”
Section: Marine Ecosystemsmentioning
confidence: 99%
“…Metabarcoding has been successfully applied in a number of studies as a powerful and repeatable method for characterizing biodiversity (Hänfling et al, ; Leray & Knowlton, ). The flexibility of metabarcoding protocols allows the analyses of a wide range of sample types (sediment: Guardiola et al, , substrate: Wangensteen et al, , seawater: Bakker et al, , bulk invertebrate samples: Elbrecht & Leese, , stomach contents: Siegenthaler, Wangensteen, Benvenuto, Campos, & Mariani, and scat: Berry et al, ), to more recent approaches that utilize natural environmental samplers as a tool to survey marine biodiversity such as utilizing the diet profiles of benthic scavengers to assess fish diversity or harnessing water‐filtering sponges to sample environmental DNA (natural sampler DNA—nsDNA; Mariani, Baillie, Colosimo, & Riesgo, ; Siegenthaler, Wangensteen, Soto, et al, ). While metabarcoding of environmental samples has many limitations associated with primer performance, bioinformatic workflows and study design (Elbrecht, Hebert, & Steinke, ), it overcomes many morphology‐based challenges in identifying species at different levels (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…PISCO’s monitoring approach consists of swath sampling to quantify the density and abundance of the macroalgae, invertebrates and fishes that comprise kelp forest communities. A Venn diagram was used to visualize genus‐level gamma richness of WRMS, Seanet and PISCO data sets using venneuler in R (Wilkinson & Urbanek, ). Further, WRMS and PISCO community assemblage structures were compared via rank abundance (phylum‐level).…”
Section: Methodsmentioning
confidence: 99%